Determinants of functional specialisation in EU countries - Aleksandra Kordalska; Magdalena Olczyk (The Vienna Institute for International Economic Studies (wiiw), 2023)
This paper aims to identify factors that determine functional specialisation (FS) in global value chains (GVCs) in European Union countries. We focus on fabrication and R&D as two opposite business functions in terms of their character and their potential of creating value-added. To make our results robust two different approaches to measuring functional specialisation are used - an FDI-based approach and a trade-based approach. To assemble a relative functional specialisation index, for each approach we use the same metric - a revealed comparative advantages index. Our results suggest a positive effect of wages on specialisation in an R&D function, and a negative impact on FS in fabrication. Increasing labour productivity boosts both specialisation in fabrication and in R&D. The results are robust to different model specifications and different time intervals. The instrumental variables method allows us to interpret the results as causal relationships. Additionally, human capital and labour skills foster FS in R&D (only in FDI data), and growing employment makes FS in fabrication increase. The growth of GDP per capita positively affects functional specialisation in R&D activities. Among GVC participation measures, we confirm the importance of increasing backward linkages to explain the boost in fabrication activities. Dividing a full sample into a group of EU15 countries and a group of Central Eastern European countries we observe that patterns for the EU15 are similar to those for the full sample, while for CEE countries wages are insignificant and labour productivity affects FS in fabrication only.
Keywords: F15; F21; F23; F63; L23; 330; functional specialisation; global value chains; smile curve; factory economy; headquarters economy